γ-γ Sum-Coincidence Effects on Relative γ-Ray Intensities in the Decay of 147Nd-147Pm - Ghumman, S.S.; Singh, Charanjeet; Singh, Sukhpal (Asian Journal of Chemistry, 2010)
The decay scheme of 147Pm has been studied precisely to provide more detailed and accurate experimental information of level structure and linking em-transitions in the decay. The γ-γ sum-coincidences are found significant in most of the transitions as intensities of 410, 594, 680 and 685 keV transitions are largely affected. The intensity of 594 keV transition has gained 23 % summing contributions from (196 + 398) keV and (275 + 319) keV transitions. The levels at 91, 410, 489, 531, 680 and 686 keV are established whereas none of the transitions linking the levels at 182, 228, 276, 319, 408 and 725 keV are observed.